2017
DOI: 10.4184/asj.2017.11.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Spinal Subdural Lesions Following Lumbar Spine Surgery: Prevalence and Risk Factors

Abstract: Study DesignRetrospective case–control studyPurposeTo clarify the prevalence and risk factors for spinal subdural lesions (SSDLs) following lumbar spine surgery.Overview of LiteratureBecause SSDLs, including arachnoid cyst and subdural hematoma, that develop following spinal surgery are seldom symptomatic and require reoperation, there are few reports on these pathologies. No study has addressed the prevalence and risk factors for SSDLs following lumbar spine surgery.MethodsWe conducted a retrospective analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…ey identified SSDLs in 30% of the 410 cases of lumbar spine surgery. [7] Mattei et al reported a case of acute SSDH after vertebroplasty. [6] de Beer et al showed that spontaneous SSDHs were predominantly located in the thoracic spine and correlated with acute paraparesis/ paraplegia; over 40% was caused by a coagulation defect, most frequently due to Coumadin.…”
Section: Discussionmentioning
confidence: 99%
“…ey identified SSDLs in 30% of the 410 cases of lumbar spine surgery. [7] Mattei et al reported a case of acute SSDH after vertebroplasty. [6] de Beer et al showed that spontaneous SSDHs were predominantly located in the thoracic spine and correlated with acute paraparesis/ paraplegia; over 40% was caused by a coagulation defect, most frequently due to Coumadin.…”
Section: Discussionmentioning
confidence: 99%
“…A postoperative sSDH is a very rare complication in particular after an extraforaminal herniation resection with a Wiltse approach. 10,11 In most cases, an intradural hematoma is associated with trauma, vascular malformations, tumors, traumatic lumbar puncture, or anticoagulation therapy. 7,12,13 We presented a case of a 58-year-old woman with an intradural hematoma after resection of a left-sided extraforaminal disk herniation at L5/S1 by an extraforaminal Wiltse approach.…”
Section: Discussionmentioning
confidence: 99%
“…While epidural hematomas are a relatively common cause of symptoms after trauma or surgery [2], subdural hematomas, by contrast, are very rare. Acute spinal subdural hematomas have been reported following lumbar punctures [3], spinal [4] and cranial surgery [5], and trauma [6], with spontaneous hemorrhages relatively uncommon. The few spontaneous hemorrhages reported in the literature include patients with bleeding disorders, those on anticoagulant therapy [1], and underlying lesions, such as vascular malformations or tumors [7].…”
Section: Introductionmentioning
confidence: 99%